PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT NASMOCO MAGELANG - Mafrokhah, Tri Rahayu; Nugraha, Hari Susanta; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2015)
Business global era requires companies to have employees who are high quality and have a good performance . Compensation received by employees and the implementation of career development is a factor that can improve employee performance. PT Nasmoco Magelang is one car company Toyota which has a fairly high level of sales. Based on preliminary survey found problems regarding compensation and career development that is not in accordance with the wishes of employees . The purpose of this study was to determine the effect of variable compensation and career development partially and simultaneously on employee performance. The analysis tool used is quantitative analysis includes correlation , simple linear regression , multiple linear regression , koerfisien test of determination ( R2 ) and the significance test with SPSS 16.0 . The test results demonstrate the compensation and career development and simultaneous partial effect on employee performance. Simultaneously compensation and career development affects the performance of employees is the coefficient of determination of 51.4 %. Based on the results of multiple linear regression test career development have the greatest influence on employee performance with a significance of 0.000. PT Nasmoco Magelang is expected to adjust the amount of bonuses and incentives with the performance of each employee, As well as informing CAN do career development To employees well and that more attention to education